Deriving dichotomous outcome measures from continuous data in randomised controlled trials of analgesics: Verification from independent data - Moore, A; McQuay, H; Gavaghan, D (1997)
A previously established relationship for deriving dichotomous from continuous information in randomised controlled trials (RCTs) of analgesics has been tested using an independent data set. Individual patient information from 18 RCTs of parallel-group design in acute postoperative pain (after abdominal, gynaecological and oral surgery) was used to calculate the percentage of the maximum possible pain relief score (%maxTOTPAR) and the proportion of patients with andgt;50%maxTOTPAR for the different treatments, The relationship between the measures was investigated in 85 treatments with over 3400 patients. In 80 of 85 treatments (94%) agreement between calculated and actual number of pa